Pacific‐Panthalassic Reconstructions: Overview, Errata and the Way Forward. (29th July 2019) - Torsvik, Trond H.; Steinberger, Bernhard; Shephard, Grace E.; Doubrovine, Pavel V.; Gaina, Carmen; Domeier, Mathew; Conrad, Clinton P.; Sager, William W.
Abstract: We have devised a new absolute Late Jurassic‐Cretaceous Pacific plate model using a fixed hot spot approach coupled with paleomagnetic data from Pacific large igneous provinces (LIPs) while simultaneously minimizing plate velocity and net lithosphere rotation (NR). This study was motivated because published Pacific plate models for the 83.5‐ to 150‐Ma time interval are variably flawed, and their use affects modeling of the entire Pacific‐Panthalassic Ocean and interpretation of its margin evolution. These flaws could be corrected, but the revised models would imply unrealistically high plate velocities and NR. We have developed three new Pacific realm models with varying degrees of complexity, but we focus on the one that we consider most realistic. This model reproduces many of the Pacific volcanic paths, modeled paleomagnetic latitudes fit well with direct observations, plate velocities and NR resulting from the model are low, and all reconstructed Pacific LIPs align along the surface‐projected margin of the Pacific large low shear wave velocity province. The emplacement of the Shatsky Rise LIP at 144 Ma probably caused a major plate boundary reorganization as indicated by a major jump of the Pacific‐Izanagi‐Farallon triple junction and a noteworthy change of the Pacific‐Izanagi seafloor spreading direction at around chron M20 time. Key Points: We devised a new absolute Late Jurassic‐Cretaceous Pacific plate model This study was motivated because published Pacific plate models (83.5–150 Ma) are variably flawed The emplacement of the Shatsky Rise Large Igneous Province at 144 Ma caused a major plate boundary reorganization